Microwave-Assisted Catalytic Optimization of Pineapple Industrial Waste Conversion for Bioethanol Production - Livia Rhea Alvita; Vida Elsyana; Rahmat Hidayat; Amelia Sri Rezki; Silvia Malum Padang; Rafli Rustiawan Jody (Bogor Agricultural University, Indonesia, 2026)
Pineapple peel waste has high potential as a bioethanol feedstock due to its abundant lignocellulosic content, although its utilization remains limited to compost and animal feed. This study aims to optimize the catalytic conversion of pineapple peel waste into bioethanol using a microwave-assisted system with homogeneous (HCl) and combined acid–zeolite catalysts. The process involved physical pretreatment, delignification using 1% NaOH and 2% Al₂O₃ (135 W, 40 min), catalytic hydrolysis, four-day fermentation, and distillation. Characterization using FTIR and SEM–EDX revealed significant chemical and morphological changes. Lignin content decreased from 30.98% to 14.36%, while cellulose and hemicellulose increased to 32.82% and 40.67%, respectively. Hydrolysis with 0.5 N HCl and zeolite for 45 minutes produced the highest reducing sugar concentration of 18.36 g/L and total dissolved solids of 4.05 °Brix. Two-way ANOVA analysis confirmed that catalyst concentration, hydrolysis time, and their interaction had a significant effect on reducing sugar yield (p<0.05). Fermentation produced 7.9% ethanol content (GC–MS) and 6.51% yield. Overall, the integration of microwave-assisted hydrolysis and acid–zeolite catalysis effectively enhanced lignocellulosic conversion efficiency, demonstrating a promising approach for sustainable bioethanol production.